Factors Causing Smoking Habits in Football Athletes - Fazri Fadhilah Hidayat; Kartono Pramdhan; Ricky Ferrari Valentino Ward (STKIP Pasundan Press, 2025)
Abstract This study aims to determine what factors cause the habit of smoking in soccer athletes. The research method used is a qualitative method. This research method is used because this study is qualitative and the data collection tool uses an open questionnaire. The instrument used is Descriptive Qualitative using an open-ended instrument. The population of this study was 30 SSB soccer athletes. And for the sample were 20 SSB soccer athletes. The sampling technique used in this study was purposive sampling. The results of the study of the factors causing the habit of smoking in SSB Putra Tunggal Kansar soccer athletes are influenced by several factors such as habits, self-confidence, experimenting and peers. The description of this conclusion is as follows: Habits, self-confidence, experimenting and peers influence the smoking behavior of SSB Putra Tunggal Kansar students. Keywords: Smoking,football